TEACHER’S STRATEGIES IN TEACHING WRITING DESCRIPTIVE TEXT AT 10TH GRADE OF SMA NEGERI 5 KOTA SERANG - Vina Agustina; Yusti Fargianti; Akhmad Baihaqi (Bajang Institute, 2022)
The aim of this research is to investigate the teacher's strategies in teaching writing descriptive text at 10th grade of SMA Negeri 5 Kota Serang. This research applied a qualitative method by using case study design. The required data were collected through observation, interview, and questionnaire. The participant of this research was an English teacher of SMA Negeri 5 Kota Serang. The findings of the data analysis showed that the English teacher in SMA Negeri 5 Kota Serang applied several strategies when teaching writing descriptive text in classroom, such as cooperative learning or discussion, brainstorming, demonstration, and games. Cooperative learning or discussion used as group discussion with 3-4 students, brainstorming as warming up and creates the enjoyment of the class, demonstration as method to demonstrate about descriptive text in general and detail such as grammar and tense, games are used as ice breaking in class for attract the student’s attention. Educational games based on technology were used as strategy. The participant used applications for educational games for adapting to the current situation that requires students or teachers to use technology. However, with these strategies the students can understand the material of descriptive text material optimally, and make the class atmosphere more interesting.